Tren Penelitian Teknologi Digital dalam Pendidikan: Kajian Sistematis Literatur dan Analisis Bibliometrik 2019–2025 - Hamdan Siregar; Maslina Daulay; Nursyaidah Nursyaidah (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
The transformation of education through the use of digital technology has become a crucial aspect in the development of education over the past decade. Technological developments such as e-learning, blended learning, mobile learning, and learning analytics play a strategic role in improving the quality of the learning process. Through a systematic review of Scopus-based literature from 2020 to 2025 using the Systematic Literature Review (SLR) method and bibliometric analysis, this study maps the trends in the use of digital technology, the dominant types of technology, and the integration challenges faced. The findings show an increase in the number of publications each year with a primary focus on digital learning technology, particularly in countries such as the United States, China, and Indonesia. Although digital technology has proven effective in increasing motivation and learning outcomes, its successful implementation still depends on the readiness of teacher competencies, infrastructure, and the reduction of the digital divide. This study provides a comprehensive overview of global developments and offers important directions for further research and the development of digital technology-based education policies so that educational transformation can be optimal and inclusive.